THE MEANING OF SITOU TIMOU TUMOU TOU AS A MODEL OF WOMEN EMPOWERMENT MANAGEMENT IN MAPALUS HOUSE IN SOUTHEAST MINAHASA, NORTH SULAWESI - Treesje Imran; Laurens Mambu; Beatrix Lapalelo; Yongker Baali; Patricia Jeaneth Cyntia Kojongian (Sekolah Tinggi Ilmu Ekonomi Sultan Agung, 2023)
Si Tou Timou Tumou Tou is a philosophy of the Minahasa people, meaning that humans live to humanize others. The term